Synthesis of Push-Pull Azulene-Based Compounds - Merkhatuly, N.; Iskanderov, A.N.; Abeuova, S.B.; Iskanderov, A.N. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Nowadays, non-benzenoid aromatic hydrocarbons are widely used as synthons for the production of new organic semiconductors with interesting photophysical characteristics. For instance, a non-benzoid azulene hydrocarbon with a polar structure, a narrow energy gap between the highest free and lowest occupied molecular orbital and the ability to form stable ions can be intended as a structural moiety for the synthesis of new conjugated compounds with important optical and electronic properties. The article discusses the synthesis and investigation of the optical properties of new push-pull azulene-based compounds. It shows that Friedel- Crafts acylation is used as the key reaction for the synthesis of methyl- and phenyl-dicyanovinylated azulenes. The interaction proceeds regioselectively at the C1 and C3 positions of the five-membered azulene ring. It is identified that the synthesis of push-pull dicyanovinylated azulenes by Knoevenagel condensation of azulenyl ketones with malononitrile proceeds easily in Py and DMSO. The UF-vis spectra of the obtained azulene push-pull compounds demonstrated strong electron absorption in the visible zone with λmax at 410, 430, 434 and 452 nm associated with transport of charge between the donor azulene ring and the acceptor dicyanovinyl group. The scheme of resonant structures shows the mechanism of intramolecular donoracceptor interaction. The structure of the synthesized push-pull dicyanovinylated nonazulenes was elucidated using modern physicochemical and spectroscopic research methods.
Keywords: functional materials; organic semiconductors; ketoazulene; diketoazulene; bis-dinitrilevinylazulene; mono-dinitrileazulene; donor-acceptor azulenes; π-conjugated systems